Testing the Factors that Determine the Profitability of Banks with a Dynamic Approach: Evidence from Turkey - Mesut Doğan; Feyyaz Yildiz (Journal of Central Banking Theory and Practice, 2023)
The present study aims to identify the internal and external factors that affect the profitability of banks operating in Turkey. For this purpose, the study used data from 23 public, private, and foreign banks, covering the period from 2007 to 2020. Two dependent variables were used as the profitability indicators of banks, namely, the Return on Equity (ROE) and the Return on Assets (ROA). In order to increase the reliability of the models developed during the study, Dynamic Generalized Method of Moments (GMM) and Fixed Effect Model (FEM) were applied. Results of the analysis indicate a positive and statistically significant relation between inflation rate and GDP growth rate, and ROA and ROE. According to the results of GMM, there was a positive relation between ROA and ROE, and 1-year and 2-year lagged ROA and ROE. This situation may be explained by the fact that profits acquired in the Turkish banking sector are steady. ROA and ROE were observed to have a positive relation with inflation rate and economic growth rate. In other words, the increase in inflation rate and GDP growth rate positively affect profitability of public, private, and foreign banks.
Keywords: 330; Bank Profitability; Turkish Banking; Dynamic Approach